Pilot Study on The Nutritional Assessment and Intervention Kiosk: Utility and User-Centric Performance Evaluation in Combating Malnutrition - Shyamli Thakur; Samir Bhargava; Mansi Gauniyal (National Journal of Community Medicine)
Background: To combat double burden of malnutrition, Nutritional Assessment and Intervention Kiosk (NAIK) has been proposed as a potential solution. which provides personalized nutritional assessments and interventions, leveraging the latest digital health technologies. The present pilot study reports user-centric performance evaluation and utility of NAIK to determine its impact on managing malnutrition.